Crop Production Summary - 2021 - G. Sassenrath; L. Mengarelli; J. Lingenfelser; M. Knapp; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2022)
Soybean and corn varieties were tested in replicated field trials at the Southeast Research and Extension Center in Parsons through the Kansas State University variety testing program. In total, 26 corn varieties and 28 soybean varieties were tested. Weather during 2021 was near average for both rainfall and temperature, though there were periods of high rainfall and high temperatures. Corn and soybean production was also near average, both across the state and in the cultivar trials at Parsons.
Keywords: crop variety testing; soybeans; full season; double cropped; variety trials; corn production; soybean production